1999
DOI: 10.1002/(sici)1096-9926(199909)60:3<143::aid-tera9>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine exposure to clomiphene and neonatal persistent hyperplastic primary vitreous

Abstract: A 4‐year‐and‐10‐month‐old girl was diagnosed shortly after birth with persistent hyperplastic primary vitreous (PHPV). Her mother took clomiphene 100 mg daily for approximately 4 weeks and discontinued the drug once she had a positive pregnancy test. The exact time of gestation was not clear. Clomiphene is an estrogen antagonist effective in the treatment of anovulation. Various ocular side effects have been described in women taking the drug, including decreased vision, mydriasis, flashing lights, central sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Mitwally et al (21) reported favorable pregnancy outcomes and a low multiple-gestation rate for the use of aromatase inhibitors for ovarian stimulation. Clomiphene citrate has been reported to elicit various ocular side effects in 1.5%-10% of patients taking it (22). Toxicology studies have shown that anastrozole is well tolerated at 1 and 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Mitwally et al (21) reported favorable pregnancy outcomes and a low multiple-gestation rate for the use of aromatase inhibitors for ovarian stimulation. Clomiphene citrate has been reported to elicit various ocular side effects in 1.5%-10% of patients taking it (22). Toxicology studies have shown that anastrozole is well tolerated at 1 and 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Information on the teratogenic capacity of letrozole in humans is lacking, but animal studies have shown that low doses of letrozole are effective in inducing noxious effects on the developing conceptus (22). In the rat, teratogenic effects, including fetal domed head and cervical/centrum vertebral fusion, resulted from exposure to 0.03 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Mitwally et al (23) reported favorable pregnancy outcomes and low multiple gestation rates with aromatase inhibitors for ovarian stimulation. Clomiphene citrate has been reported to elicit various ocular side effects in 1.5% to 10.0% of patients taking CC (22).…”
Section: Discussionmentioning
confidence: 99%
“…A case report of Persistent Hyperplastic Primary Vitreous (PHPV) in an exposed offspring from clomiphene is an example of such an anecdotal report without any population-based data regarding the frequency of such effects. 79 The breast cancer medication tamoxifen is a selective-estrogen receptor modulator 31 that is structurally similar to clomiphine and has been used as a fertility agent and breast cancer treatment medication. 80 Ocular side effects of tamoxifen are varied and include increased risk of posterior subcapsular cataracts, optic neuropathy, and foveal cystoid spaces.…”
Section: Contraception and Hormone Therapy (Ht) Effects On Retinal Dymentioning
confidence: 99%